2011
DOI: 10.4236/gsc.2011.12006
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Bis-enaminones by KHSO4-assisted Facile Michael Addition-elimination Reaction of 3-(dimethylamino)-1-phenylprop-2-en-1-ones with Diamines in Water

Abstract: Abstract3-(Dimethylamino)-1-phenylprop-2-en-1-ones (formylated acetophenones) 1 reacted with aliphatic diamines in water assisted by KHSO 4 to give bis-enaminones 2a-h in good yields. Compound 1 also reacted with o-phenylenediamine under similar conditions to produce bis-enaminones 3 instead of benzodiazepines 4 in excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Though the enaminone formed by primary amine is commonly recognized as one kind of dynamic bond, 40 little attention has been paid to secondary amine based enaminone, which seems more stable. To Scheme 3A), 41,42 which gave us an inspiration to get exact degradation products by dealing polymers with Lewis acid and primary amine. After optimization, it was found that Fe 3+ can catalyze the reaction of P1a2a with aniline at room temperature, but only 54% of 10 can be separated out.…”
Section: Resultsmentioning
confidence: 99%
“…Though the enaminone formed by primary amine is commonly recognized as one kind of dynamic bond, 40 little attention has been paid to secondary amine based enaminone, which seems more stable. To Scheme 3A), 41,42 which gave us an inspiration to get exact degradation products by dealing polymers with Lewis acid and primary amine. After optimization, it was found that Fe 3+ can catalyze the reaction of P1a2a with aniline at room temperature, but only 54% of 10 can be separated out.…”
Section: Resultsmentioning
confidence: 99%
“…A similar approach was used for the synthesis of the bis(1,2,3,4‐tetrahydropyrimidines) ( 16a – d ) and 1,2‐bis(5‐benzoyl‐3,6‐dihydro‐2 H ‐1,3‐oxazine‐3‐yl)‐ethane ( 17 ), starting from the previously reported bis (secondary enaminone) 15 , as depicted in Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 20a , 20b , 21a , 21b , 22 , 23a , 23b , 24 , and 25 are of limited solubility in common 1 H NMR solvents. Compounds 1 , 2a , 2b , 2c , 3a – 3c , 15 , and 18 were prepared as previously described.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In continuation with our efforts for the development of novel synthetic strategies assisted by KHSO 4 [42,43], we report herein a facile environment-friendly, one-pot two-step regioselective synthesis for 3,7-diarylpyrazolo[1,5-a]pyrimidines related to zaleplon and 3,6-diarylpyrazolo[1,5-a]pyrimidin-7-amines.…”
Section: Introductionmentioning
confidence: 98%